Chemopreventive and therapeutic potential of curcumin in esophageal cancer: Current and future status. Issue 6 (12th November 2018) - Hesari, AmirReza; Azizian, Mitra; Sheikhi, Alireza; Nesaei, Abolfazl; Sanaei, Shahin; Mahinparvar, Nazanin; Derakhshani, Maryam; Hedayt, Pegah; Ghasemi, Faezeh; Mirzaei, Hamed
Abstract : Esophageal cancer is a common malignant tumor with an increasing trend during the past three decades. Currently, esophagectomy, often in combination with neoadjuvant chemo‐ and radiotherapy, is the cornerstone of curative treatment for esophageal cancer. However, esophagostomy is related to significant risks of perioperative mortality and morbidity, as well as lengthy recovery. Moreover, the adjuvant therapies including chemotherapy and radiotherapy are associated with numerous side effects, limiting compliance and outcome. The dietary agent curcumin has been extensively studied over the past few decades and is known to have many biological activities especially in regard to the prevention and potential treatment of cancer. This review summarizes the chemo‐preventive and chemotherapeutic potential of curcumin in esophageal cancer in both preclinical and clinical settings.